2010
DOI: 10.1261/rna.2395211
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the 1918 pandemic H1N1 influenza A virus as studied by codon usage patterns and phylogenetic analysis

Abstract: The pandemic of 1918 was caused by an H1N1 influenza A virus, which is a negative strand RNA virus; however, little is known about the nature of its direct ancestral strains. Here we applied a broad genetic and phylogenetic analysis of a wide range of influenza virus genes, in particular the PB1 gene, to gain information about the phylogenetic relatedness of the 1918 H1N1 virus. We compared the RNA genome of the 1918 strain to many other influenza strains of different origin by several means, including relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 40 publications
2
27
0
3
Order By: Relevance
“…14,40,41 Furthermore, a relatively large number of codons with (nearly) absolute conservation of wobble positions suggests the actual number of base-pairing interactions to be larger than described in this work, which considers only the structures reliably supported by covariation analysis. On the other hand, the locations of structures (Fig.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…14,40,41 Furthermore, a relatively large number of codons with (nearly) absolute conservation of wobble positions suggests the actual number of base-pairing interactions to be larger than described in this work, which considers only the structures reliably supported by covariation analysis. On the other hand, the locations of structures (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…41). Unfortunately, the low number of covariation events detected in influenza virus RNA excludes an application of statistics based on counting of covariations occurring in multiple branches of an evolutionary tree in order to filter out spurious coincidences upon speciation.…”
Section: Discussionmentioning
confidence: 99%
“…A switch in receptor specificity from avian (␣-2,3-linked) to human (␣-2,6-linked) sialic acids as well as stabilization of the stalk region to allow endosomal membrane fusion at the optimal pH is crucial for efficient transmission between mammals (67, 68) and host adaptation (102). Other important factors include appropriate HA glycosylation, the length of the stalk region in the neuraminidase (NA), and specific differences in codon usage (103)(104)(105)(106).…”
Section: Figmentioning
confidence: 99%
“…During that year in the United States, outbreaks of respiratory disease occurred simultaneously in humans and swine; whether the H1N1 virus jumped species from humans to pigs or vice versa remains unclear. Recently, it has been suggested that the 1918 pandemic virus was derived from an influenza virus of swine origin and that the precursor of this virus was a descendant of a distinct avian H1N1 virus (1). The H1N1 virus became established in domestic pigs after 1918, forming the classical swine H1N1 lineage, and continued to circulate as the dominant influenza virus in North American swine populations until 1998 (7,29).…”
mentioning
confidence: 99%